STOCK-FLOW CONSISTENT (SFC) AS A SUITABLE APPROACH TO MODELING THE NEW DEVELOPMENTALIST FRAMEWORK - Costa Santos, Julio Fernando (Práticas de Administração Pública, 2022)
This paper explores the theoretical bases of New Developmentalism, highlighting its core propositions. Evaluates the first effort of mathematical proposition of a New Developmentalist prototype model. It explores how the integration of the current model with a version using the Stock-Flow Consistent approach would look like and how this methodology could help to solve some gaps left behind. Finally, a projection for a new research agenda using sectoral and microeconomic details is pointed out as a possible work front.